Original paperPatterns of care study of brachytherapy in New South Wales: malignancies of the uterine corpus - Thompson, Stephen R.; Delaney, Geoff P.; Gabriel, Gabriel S.; Barton, Michael B. (Journal of Contemporary Brachytherapy, 2015)
Purpose: There are limited data at a population level on adjuvant brachytherapy (BT) practice for uterine corpus malignancies. The aims of the current study were to describe BT practice for this disease in New South Wales (NSW), to assess quality of BT, and to determine if a caseload effect on quality exists. Material and methods: Patient, tumour, and treatment related data were collected from all nine NSW radiation oncology departments that treated patients with BT. Included patients had malignancy of the uterine corpus with treatment including BT. Brachytherapy quality was assessed using published quality benchmarks. Higher gynaecological BT caseload departments were compared with lower caseload departments. Results: One hundred sixty-three NSW residents with gynaecological cancer were treated with BT. The four higher gynaecological BT caseload departments treated a median of 25.5 NSW residents (range 22-38), compared to median 10 (range 3-18) in the five lower caseload departments. Seventy-five patients underwent BT for uterine malignancies. Most patients had early stage endometrioid disease and were treated adjuvantly with intravaginal cylinders using high-dose-rate BT. Doses were in accordance with guideline recommendations in 83% of cases, and BT was appropriately indicated in 76% of cases. Higher caseload departments were more likely to treat with guideline doses (96% vs. 53%, p < 0.001) but there was no difference in compliance rate with treatment indications (p = 0.75). Conclusions: Brachytherapy patients, techniques, and numbers/unit for uterine corpus malignancies were similar in NSW compared to the USA but more dispersed than in Western Europe. Doses prescribed may not be optimal in lower gynaecological BT caseload departments – the significance of this represents an area in which more research is needed.